Exploring the social value of Public Health Institutes: An international scoping survey and expert interviews - Ashton, Kathryn; Green, Liz; Clemens, Timo; Parry-Williams, Lee; Dyakova, Mariana; Bellis, Mark A. (Frontiers in Public Health, 2022)
Introduction Making the case for investing in preventative public health by illustrating not only the health impact but the social, economic and environmental value of Public Health Institutes is imperative. This is captured by the concept of Social Value, which when measured, demonstrates the combined intersectoral value of public health. There is currently insufficient research and evidence to show the social value of Public Health Institutes and their work across the life course, population groups and settings, in order to make the case for more investment. Methods During July 2021, a quantitative online self-administered questionnaire was conducted across international networks. Semi-structured interviews were also carried out with nine representatives to gain a deeper understanding. A thematic analysis was undertaken on the data collected. Results In total, 82.3% (n = 14) were aware of the terminology of social value and 58.8% (n = 10) were aware of the economic method of Social Return on Investment. However, only two Institutes reported capturing social and community impacts within their economic analysis and only 41.2% (n = 7) currently capture or measure the social value of their actions. Interviews and survey responses indicate a lack of resources, skills and buy-in from political powers. Finally, 76.5% (n = 12) wanted to do more to understand and measure wider outcomes and impact of their actions. It was noted this can be achieved through enhancing political will, developing a community of best practice and tools. Conclusion This research can inform future work to understand how to measure the holistic social value of Public Health Institutes, in order to strengthen institutional capacity and impact, as well as to achieve a more equitable society, and a more sustainable health system and economy, making the case for investing in public health, as we recover from COVID-19.